CN and NH Bond Metathesis Reactions Mediated by Carbon Dioxide. Issue 12 (3rd June 2015) - Wang, Yehong; Zhang, Jian; Liu, Jing; Zhang, Chaofeng; Zhang, Zhixin; Xu, Jie; Xu, Shutao; Wang, Fangjun; Wang, Feng
Abstract Herein, we report CO2‐mediated metathesis reactions between amines and DMF to synthesize formamides. More than 20 amines, including primary, secondary, aromatic, and heterocyclic amines, diamines, and amino acids, are converted to the corresponding formamides with good‐to‐excellent conversions and selectivities under mild conditions. This strategy employs CO2 as a mediator to activate the amine under metal‐free conditions. The experimental data and in situ NMR and attenuated total reflectance IR spectroscopy measurements support the formation of the N‐carbamic acid as an intermediate through the weak acid–base interaction between CO2 and the amine. The metathesis reaction is driven by the formation of a stable carbamate, and a reaction mechanism is proposed.